KEANEKARAGAMAN IKAN DI SUNGAI SULUP KECAMATAN RIMBO PENGADANG KABUPATEN LEBONG PROVINSI BENGKULU - Pariyanto Pariyanto; Endang Sulaiman; Rukiah Lubis (Jurnal Biosilampari : Jurnal Biologi, 2021)
This study aims to determine the diversity of fish species in Sulup River, Rimbo Pengadang District, Lebong Regency, Bengkulu. The Research was conducted from in April-May 2020. The method used in this study is a direct survey method. The sampling method used is purposive sampling by dividing the research station into 3 stations based on river conditions. The types of fish found in the Sulup River Rimbo Pangadang District Lebong Regency Bengkulu Province were found as many as 4 orders, 4 families with 8 species namely species Mystus singaringan, Angullia marmorata, Osteochilus vittatus, Hampala macrolepidota, Barbonymus gonionotus, Schismatorhynchos heterorhynchos, Rasbora argyrotaenia and Mastacembelus armatus. The ecological conditions in the Sulup river have a temperature of 230C, a depth of 1.5 m, 45 cm river clarity, water pH 7, flow velocity 0.66 m/sec. Sulup River has a diversity index of 0.840, so the diversity index is low.